2014
DOI: 10.7257/1053-816x.2014.34.6.318
|View full text |Cite
|
Sign up to set email alerts
|

Student Nurse Understanding Of the Psychosocial Impact Of Urinary Incontinence

Abstract: Acknowledgement:The authors wish to thank Jane Schade Henderson, PhD, RN, for the use of her tool -the Urinary In conti nence Scales -and her valuable insight regarding urinary incontinence-associated attitudes, beliefs, practice, and knowledge. ResearchThis study examined the attitudes of baccalaureate student nurses regarding the care of the incontinent patient and to explore their beliefs of the psychosocial impact urinary incontinence has on the affected adult patient. It explored the beliefs and attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
(35 reference statements)
3
4
0
1
Order By: Relevance
“…This finding may be due to the fact that they had a fresh memory of UI knowledge because the topic they studied was more recent than the year 5 nursing students. The achievement of UI knowledge scores is similar to a study conducted in the United States 22 but better than a study of nursing students conducted in China. 23 The similarity between Hong Kong and the United States reflects a similar emphasis on UI in the syllabuses of their undergraduate nursing programs.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This finding may be due to the fact that they had a fresh memory of UI knowledge because the topic they studied was more recent than the year 5 nursing students. The achievement of UI knowledge scores is similar to a study conducted in the United States 22 but better than a study of nursing students conducted in China. 23 The similarity between Hong Kong and the United States reflects a similar emphasis on UI in the syllabuses of their undergraduate nursing programs.…”
Section: Discussionsupporting
confidence: 67%
“…Limited evidence suggests nursing students have positive attitudes toward UI 22,23. For example, Hutchings and Sutherland22 surveyed 52 junior and senior student nurses from 2 universities and found that they had a positive attitude toward caring of patients with UI. A study of 1313 Chinese nursing students found that approximately 72% had a positive attitude toward UI care, though they also found low knowledge of UI care 23…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the findings, Hong Kong nursing students achieved a moderate level in urinary incontinence knowledge. It was similar to the study conducted in US where junior and senior nursing students achieved 71% correct rate [12] but better than the nursing students in China, who achieved 49.9% correct answers [13]. This result suggests that nursing education in Hong Kong share similar emphasis on urinary continence care with their counterparts in western countries.…”
Section: Discussionsupporting
confidence: 85%
“…We screened 2307 titles, 429 abstracts and 107 full texts. We excluded 66 out of 107: reviews [50][51][52][53][54][55]; long term care and acute hospitalisation [56][57][58][59][60][61][62][63][64][65][66]; faecal incontinence [67][68][69][70][71][72][73][74][75][76][77][78]; family experience [79][80][81][82][83][84]; healthcare professionals' experience [85][86][87][88][89][90][91][92][93][94][95] Pelvic organ prolapse [96,97], Continence surgery [98], Post-partum pelvic floor dysfunction …”
Section: Electronic Sources Medlinementioning
confidence: 99%